2010
DOI: 10.1007/s00268-010-0398-3
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of Malignancy in Thyroid Nodules with Indeterminate Fine‐Needle Aspiration Cytology After Negative 18F‐Fluorodeoxyglucose Positron Emission Tomography: Interim Analysis

Abstract: Background In all, 20% of fine‐needle aspiration (FNA) biopsies of thyroid nodules have an indeterminate diagnosis; of these, 80% are found to be benign after thyroidectomy. Some previous reports indicate that positron emission tomography (PET) with 18F‐fluorodeoxyglucose (FDG) imaging may predict malignancy status. We now report results on the first 51 patients in the largest prospective study of FDG‐PET in patients with an indeterminate thyroid nodule FNA. Methods Eligible patients had a dominant thyroid nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 23 publications
2
57
2
Order By: Relevance
“…Seven previous studies have evaluated the usefulness of FDG PET for the differentiation of indeterminate nodules of the thyroid, yielding conflicting results (Kresnik et al 2003, de Geus-Oei et al 2006, Kim et al 2007, Sebastianes et al 2007, Hales et al 2008, Traugott et al 2010, Deandreis et al 2012. The sensitivity of FDG PET was 57-100%, depending on the characteristics of the patient population.…”
Section: Incidentalomas Detected By Fdg Petmentioning
confidence: 99%
“…Seven previous studies have evaluated the usefulness of FDG PET for the differentiation of indeterminate nodules of the thyroid, yielding conflicting results (Kresnik et al 2003, de Geus-Oei et al 2006, Kim et al 2007, Sebastianes et al 2007, Hales et al 2008, Traugott et al 2010, Deandreis et al 2012. The sensitivity of FDG PET was 57-100%, depending on the characteristics of the patient population.…”
Section: Incidentalomas Detected By Fdg Petmentioning
confidence: 99%
“…At present, there is no alternative algorithm for more conservative management of patients with indeterminate FNAC. Convectional USG, CT, and magnetic resonance imaging (MRI) have previously been shown to be of some value, but FDG-PET has yet to be assessed in a large prospective study [25]. Table 3 shows a comparison of series examining the utility of FDG-PET in detecting malignancy in a thyroid nodule with indeterminate FNAC findings [25,29,[37][38][39][40][41].…”
Section: Role Of Fdg-pet In Indeterminate Thyroid Lesions On Fnacmentioning
confidence: 99%
“…However, because most of these reported series were retrospective in design and the patient selection was not formally standardized, there is a need for a large, well-designed prospective study. Recently, Traugott et al [25] reported the results of 51 patients with indeterminate FNAC findings in an interim analysis of their prospective trial, which began in 2004. Their data suggested that FDG-PET was an accurate diagnostic modality for identifying malignancy in thyroid nodules Ն1 cm in diameter and with indeterminate FNAC results, with 100% sensitivity and NPV.…”
Section: Role Of Fdg-pet In Indeterminate Thyroid Lesions On Fnacmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG PET has been used but its sensitivity and specificity are questioned, although a cancer diagnosis is generally ruled out in the presence of negative result (4)(5)(6). PET imaging of a thyroid cancer-associated marker would be preferable.…”
Section: The Use Of Pet In Combination With Different Pet Tracers Likmentioning
confidence: 99%